Women and Customary Rituals in The Neres Tradition - Maulia Pratiwi; Naniek Afrilla Framanik; Ail Muldi (International Journal on Education Issues, 2025)
The purpose of this study was to describe and analyze the Neres tradition as part of a series of Seren Taun ceremonies in Kasepuhan Citorek, an Indigenous community of Banten Kidul located in the Mount Halimun Salak National Park (TNGHS). This tradition serves as a ritual of self-purification before the implementation of Seren Taun as well as believed to be able to resist reinforcements, prevent pagebluk, and maintain the fertility of agricultural products. The research uses qualitative approach with post-positivistic paradigm and ethnographic method of communication. Data were collected through observation, interviews, documentation, and triangulation. The results showed that the Neres tradition has more meaning than just the practice of physical hygiene, but is full of symbols that reflect the values of prosperity, chastity and attachment to ancestors. In-depth analysis shows that cleaned household appliances - such as hihid, seeng, Dipper, pangarih, dulang, Basom, and boboko—are not only seen as utilitarian objects, but also symbols of well-being and the continuity of domestic life. This cleansing procession affirms the role of women as Guardians of domestic harmony as well as liaisons between Indigenous values that are passed down through generations. In addition, the use of natural elements such as palias grass, ash from upstream rice, and mulang water strengthens the spiritual dimension that unites humans with the surrounding nature. Thus, the Neres tradition can be understood as a communication ritual that contains symbolic messages, affirms the central role of women in the preservation of culture, and represents the collective identity of the Kasepuhan Citorek community that persists in the midst of changing times.